Assessing the Development of Sports in Latvian Municipalities: A Pilot Study Aligned With HEPA Framework (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Municipalities play a crucial role in shaping local environments and opportunities for health-enhancing physical activity (HEPA), yet there is a lack of systematic, evidence-based assessment tools to guide and inform their efforts. By applying a standardised set of HEPA-aligned indicators, this research addresses a critical gap in understanding how local policies, infrastructure, and programmes contribute to the promotion of active lifestyles.Aim: To evaluate the current state of sports development within selected Latvian municipalities by applying a set of indicators aligned with the Health-Enhancing Physical Activity (HEPA) framework, with the purpose of identifying strengths, gaps, and opportunities to support evidence-based policy and programme improvements that promote physical activity and public health at the local level.Methods: The methodology included a self-designed sports statistics questionnaire development and the application of mathematical statistics, with data processing performed using SPSS software. To assess the development of sports in Latvian municipalities, it was essential to establish relevant statistical indicators. A sports statistics questionnaire was designed, incorporating key dimensions such as sports infrastructure, governance, and economic factors. This questionnaire was subsequently tested through a pilot study conducted in three municipalities: Liepāja, Ludza, and Saulkrasti. The study was conducted within the framework of the national research programme “Innovations, methodologies and recommendations for the development and management of the sports sector in Latvia” (IMRSportsLV) (VPP-IZM-Sports-2023/1-0001).Results: HEPA-aligned indicators are used to compare how well municipalities promote health-enhancing physical activity: presence of local physical activity policies, budget allocations for sports and HEPA initiatives, infrastructure, and environment, levels of participation in organised and informal physical activity, number of sports clubs and events, regular data collection on PA and sports, existence of local evaluation systems, use of data to guide policy.Conclusion: If these equity, health impact and monitoring, policy and programme data indicators are not measured, municipalities risk creating ineffective, inequitable, and unsustainable sports policies. Measuring these areas is essential to ensure that sports and physical activity benefit all segments of the population, contribute to public health goals, and are guided by real evidence rather than assumptions.